Presence of Dalbulus maidis (Hemiptera: Cicadellidae) and of Spiroplasma kunkelii in the Temperate Region of Argentina - Carloni, Edgardo José (2013)
“Corn stunt” is one of the main corn (Zea mays L.) diseases in the Americas and Dalbulus maidis (DeLong & Wolcott) is the key vector of the pathogen Spiroplasma kunkelii Whitcomb. In Argentina, the corn-producing area is in the temperate region, where vector and pathogen prevalence levels are unknown. In this study, the prevalence and distribution of D. maidis and S. kunkelii in the temperate region of Argentina and D. maidis overwintering ability in this region were determined. Surveys were conducted in 2005–2006 and 2006–2007 seasons to determine D. maidis and S. kunkelii presence, and in winter 2006 to determine the vector overwintering ability. The highest S. kunkelii prevalence and incidence levels were found in the transition area from the temperate to the subtropical region, related to the highest D. maidis prevalence and insects sampled per location. D. maidis adults were found in volunteer corn plants and spontaneous vegetation in autumn and winter months, which were inoculative for the pathogen S. kunkelii. This overwintering ability was related to detection of D. maidis insects in corn crops at early growth stages in the following growing season. This work emphasizes that corn stunt disease is present in the temperate region of Argentina, and this highlights the need to develop proper agronomic practices like monitoring insect vector populations and controlling voluntary plants. This study also indicates that further research is needed to understand the potential yield reduction caused by this pathogen on symptomless plants and population dynamics of the insect vector.